2016
DOI: 10.3892/ol.2016.5327
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aberrant methylated SEPT9 and NTRK3 genes in sporadic colorectal cancer patients as a potential diagnostic biomarker

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common malignancies, and the third leading cause of cancer mortality worldwide. Timely detection of CRC in patients with earlier stages provides the highest rate of survival. Epigenetic alterations are important in the occurrence and progression of CRC, and represent the primary modifications of cancer cells. Therefore, detection of these alterations in CRC cases are thought to hold great promise as diagnostic biomarkers. It has been shown that the SEPT9 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Aberrantly methylated genes are common to CRC, and these methylation changes can also be detected in ctDNA . One such ctDNA test is COLVERA, which detects hypermethylated regions within branched‐chain amino acid transaminase 1 ( BCAT1 ) and Ikaros family zinc‐finger 1 protein ( IKZF1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Aberrantly methylated genes are common to CRC, and these methylation changes can also be detected in ctDNA . One such ctDNA test is COLVERA, which detects hypermethylated regions within branched‐chain amino acid transaminase 1 ( BCAT1 ) and Ikaros family zinc‐finger 1 protein ( IKZF1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…While hypermethylation in promoter region of multiple tumor genes could be stably detected in most cancers (>90%), which makes it a feasible and specific biomarker [ 15 ]. Mounting evidence indicate that altered DNA methylation is one of the most common aberrant epigenetic modifications, which play essential roles in CRC initiation and progression [ 16 , 17 ]. Therefore, CRC specifically methylated cell-free DNA in plasma may serve as a putative biomarker for early detection, therapeutic efficacy assessment, and recurrence monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed ERG variant 2 was found in lung tumors compared to adjacent tissues, which suggested that ERG might exert an oncogenic effect in lung tumors through functions encoded by variant 2 . Aberrantly methylated NTRK3 has been demonstrated to be involved in various cancers including colorectal cancer and lung cancer . Poor survival in lung cancer was closely associated with NTRK3 .…”
Section: Discussionmentioning
confidence: 99%